Improving the coverage of the PMTCT programme through a participatory quality improvement intervention in South Africa - Chopra Mickey; Doherty Tanya; Nsibande Duduzile; Mngoma Dudu (BMC, 2009)
Abstract Background Despite several years of implementation, prevention of mother-to-child transmission (PMTCT) programmes in many resource poor settings are failing to reach the majority of HIV positive women. We report on a data driven participatory quality improvement intervention implemented in a high HIV prevalence district in South Africa. Methods A participatory quality improvement intervention was implemented consisting of an initial assessment undertaken by a team of district supervisors, workshops to assess results, identify weaknesses and set improvement targets and continuous monitoring to support changes. Results The assessment highlighted weaknesses in training and supervision. Routine data revealed poor coverage of all programme indicators except HIV testing. Monthly support to all facilities took place including an orientation to the PMTCT protocol, review of local data and identification of bottlenecks to optimal coverage using a continuous quality improvement approach. One year following the intervention large improvements in programme indicators were observed. Coverage of CD4 testing increased from 40 to 97%, uptake of maternal nevirapine from 57 to 96%, uptake of infant nevirapine from 15 to 68% and six week PCR testing from 24 to 68%. Conclusion It is estimated that these improvements in coverage could avert 580 new infant infections per year in this district. This relatively simple participatory assessment and intervention process has enabled programme managers to use a data driven approach to improve the coverage of this important programme.